Methodology to assess phasor measurement unit in the estimation of dynamic line rating - Alvarez, David L. (2018)
This paper presents a methodology to analyse the influence of both atmospheric variations in time and space and the error in synchrophasor measurements to estimate conductor temperature along an overhead line. In this methodology, expressions to compute the error propagation in the computing of temperature because of measurement errors and load variations are proposed. The analysis begins by computing overhead line's thermal and mechanical parameters using simulations of load and atmospheric conditions. Having computed these parameters, values of resistance, inductance and capacitance of the overhead line modelled by means of a π equivalent circuit are estimated, with the purpose of quantifying the sensibility of electrical parameters to changes in conductor temperature. Additionally, this analysis allows the identification of the temperature in each span along OHLs. Subsequently, the average conductor temperature is estimated using simulations of synchrophasors through the relationship between resistivity and temperature. This estimated temperature is compared with the temperature computed using atmospheric conditions to obtain the maximum error. This error is contrasted with the acceptable error margins. Thus, during the planning stage, this methodology can be used to assess PMU as a method of computing conductor temperature.